Exploring the pharmacokinetics and tolerability of cyclooxygenase inhibitor ampiroxicam: a phase I study on single and multiple oral doses - Zhao, Pengfei; Qi, Ying (Frontiers in Pharmacology, 2024)
Introduction: Ampiroxicam is a long-acting, non-steroidal anti-inflammatory drug that selectively inhibits human cyclooxygenase, effectively mitigating fever, pain, and inflammation. This study evaluated the drug's tolerability and pharmacokinetics to support personalized dosing strategies. Methods: The study involved healthy participants and focused on the pharmacokinetics of ampiroxicam. Plasma levels of piroxicam, a key metabolite of ampiroxicam, were measured using ultra-performance liquid chromatography. Piroxicam was chosen due to its integral role in ampiroxicam's metabolic pathway. The analytical method underwent rigorous validation to ensure precision and accuracy, addressing potential interference from endogenous plasma substances. Results: Participants received ampiroxicam in single doses (low, medium, and high) and multiple doses. Pharmacokinetic parameters, including AUC0–216, AUC0–∞, and Cmax, exhibited a dose-dependent increase. No significant differences were noted across the dosage groups, and sex-specific differences were minimal, with the exception of mean residence time (MRT) in the multiple-dose group, which appeared influenced by body weight variations. Discussion: The findings affirm the safety and efficacy of ampiroxicam across different dosing regimens, validating its clinical utility and potential for personalized medicine in the treatment of pain and inflammation.